The role of Filipino women's context of first birth on their fertility and socioeconomic situation - Ogena, Angelique Florendo (College of Social Sciences and Philosophy, University of the Philippines, 2015)
In the Philippines, society expects a typical family consisting of a married father and mother, and having children. Within this setup, the more favorable assumption is that the children are born within the marriage rather than outside of it. However, the growing number of nonmarital births in the country signifies that this view has been changing over time. Such case is alarming since nonmarital childbearing in other countries was found to be associated with several adverse outcomes on the mother and the child born out-of-wedlock, which could well be the case in the Philippines. In this light, this study examines the association between women’s context of first birth that is, whether their first birth was within a formal marriage or not, and their subsequent fertility and socioeconomic situation. Univariate, bivariate, and binary logistic regression analyses of the nationally representative 2013 National Demographic and Health Survey (NDHS) dataset were employed to examine this association. Specifically, the study employed data from women 25 years old and over whose live first birth occurred at least five years prior to the survey. Results reveal that one in four women have had a nonmarital first birth and that women with such births are significantly different from their counterparts who were formally married at the time of first birth in terms of selected background, fertility, and socioeconomic characteristics. On average, mothers with nonmarital first birth gave birth significantly earlier (x ̅= 19.7 years old) than their marital counterparts (x̅= 23.0 years old). Nearly half (48.5%) of mothers with out-of-wedlock first births eventually entered a formal marriage. This proportion is significantly higher for women who were below 20 years old at first nonmarital birth compared to women who were at least 20 years old at first nonmarital birth (65.4% vs. 26.4%, respectively). In terms of fertility, women with nonmarital first births have significantly more children (x̅ = 3.8) than their marital counterparts (x̅= 3.4). The same pattern holds true for women who were below 20 years old at first birth (x̅= 6.1 vs. x̅= 5.1) but not for women who first gave birth beyond their teens (x̅= 2.8 vs. x̅= 3.2). Among women who had their first birth when they were teens, those who gave birth outside marriage have 0.3 more children compared to women who were married when they gave birth. On the other hand, among women who first gave birth beyond their teen years, those who had a nonmarital birth have 0.2 to 0.4 less children than their marital counterpart. Contrary to most findings, a nonmarital first birth does not necessarily decrease the likelihood of a woman to have work and to be non-poor. Based on the results of the study, recommendations for program and policy development and for further research were presented.